Comparing skin characteristics and molecular markers of xerotic foot skin between diabetic and non-diabetic subjects: An exploratory study. Issue 4 (November 2019) - Lechner, Anna; Akdeniz, Merve; Tomova-Simitchieva, Tsenka; Bobbert, Thomas; Moga, Alain; Lachmann, Nadège; Blume-Peytavi, Ulrike; Kottner, Jan
Abstract: Background: Xerosis cutis of the feet is one of the most common skin conditions among type 2 diabetics. Whether skin dryness among diabetic patients is different from 'general' skin dryness is unclear. The overall aim was to compare the structure, function and molecular markers of dry and cracked foot skin between diabetics and non-diabetics. Methods: The foot skin of 40 diabetics and 20 non-diabetics was evaluated. A clinical assessment of skin dryness was performed and transepidermal water loss, stratum corneum hydration, skin surface pH, epidermal thickness, skin roughness, elasticity and structural stiffness were measured. Ceramides, natural moisturizing factors, histamines, proteins and molecular markers of oxidative stress were analyzed based on a non-invasive sampling method for collection of surface biomarkers. Results: The mean number of superficial fissures in the diabetic group was nearly three times higher than in the non-diabetic group (11.0 (SD 6.2) vs. 3.9 (SD 4.2)). The skin stiffness was higher in the diabetic group and the values of almost all molecular markers showed considerably higher values compared to non-diabetics. Malondialdehyde and glutathione were lower in the diabetic sample. Conclusions: The high number of superficial fissures may be based on an increased stiffness of dry diabetic foot skin combined with different concentrations of molecular markers in the stratum corneum compared to dry foot skin of non-diabetics. Highlights: The mean number of superficial fissures in the diabetic group was nearly three times higher than in the non-diabetic group. In diabetics stiffness was generally higher at all skin areas. The dorsal skin of diabetics showed higher roughness, was thinner and less hydrated, clinically possibly leading to higher fragility.